REPRESENTASI FEMINISME DAN PEMBERDAYAAN PEREMPUAN DI PULAU AMAZON LILY DALAM SERIAL ANIME ONE PIECE - Sugitanata, Arif; Siti Aminah; Muhammad Hasyied Abdurrasyied (Universitas Islam Negeri Mataram, 2024)
This research examines the representation of feminism and women's empowerment in